Women's Initial Experiences and up to a Year in Retrospect of Their Life Situation With a Confirmed Takotsubo Syndrome Diagnosis: A Single Case Study Literature Review. (June 2022) - Fridlund, Bengt; Bruteig, Eileen; Dahlviken, Rønnaug M.; Fålun, Nina; Norekvål, Tone M.
Purpose: To describe women's initial experiences and up to a year in retrospect of their life situation with a confirmed Takotsubo syndrome (TS) diagnosis.Method: A single case study literature review based on nine articles published by nurses was analyzed deductively using a nursing life dimension model.Results: All but one case was conducted on the North American continent and TS had largely affected women with previous cardiac history and had been triggered by one or two stressful life events. The biophysical life dimension manifested in distinct and troublesome inconvenience and in retrospect in fretting and grievous ailments. The emotional dimension manifested in pronounced ways and attitude-related sensations, feelings or moods while the intellectual dimension manifested in an unmanageable world of thought. The spiritual–existential dimension manifested in a life-denying view of life and the socio-cultural dimension manifested in an asocial life.Conclusions: With TS best practice in mind and a person-centered care and holistic approach, comprehensive descriptions are needed of how women identify, interpret, and use knowledge to manage their life situation. Cardiac nurses need further comprehensive descriptions to implement actions. Prior to implementation of such programs, this knowledge needs to be disseminated among cardiac nurses and evaluated in international randomized controlled trials.